2007
DOI: 10.1152/ajprenal.00397.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects on protein kinase C-β inhibition on glomerular vascular endothelial growth factor expression and endothelial cells in advanced experimental diabetic nephropathy

Abstract: Ruboxistaurin is an inhibitor of the beta isoform of protein kinase C (PKC-beta) that reduces the actions of vascular endothelial growth factor (VEGF) and attenuates the progression of diabetic retinopathy. In the glomerulus VEGF is constitutively expressed where it likely has a role in maintaining endothelial cell integrity, particularly in disease states. Given its potential use in diabetic nephropathy, we sought to determine the effects of PKC-beta inhibition on VEGF and glomerular endothelial cells in expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…A group of diabetic rats was treated with the PKC-␤ inhibitor ruboxistaurin (LY333531) as described previously. 28 This model, in which overexpression of the mouse renin gene leads to hypertension, has been shown to develop renal lesions similar to those observed in human diabetic nephropathy as early as 12 wk after STZ injection. 29 Ruboxistaurin prevents ATP binding to the active site of PKC-␤, thereby inhibiting its ability to phosphorylate substrates and functioning as a specific PKC-␤ inhibitor.…”
Section: Pkc-␤ Inhibition In Vivo Prevents Akt S473 Phosphorylation Imentioning
confidence: 64%
See 2 more Smart Citations
“…A group of diabetic rats was treated with the PKC-␤ inhibitor ruboxistaurin (LY333531) as described previously. 28 This model, in which overexpression of the mouse renin gene leads to hypertension, has been shown to develop renal lesions similar to those observed in human diabetic nephropathy as early as 12 wk after STZ injection. 29 Ruboxistaurin prevents ATP binding to the active site of PKC-␤, thereby inhibiting its ability to phosphorylate substrates and functioning as a specific PKC-␤ inhibitor.…”
Section: Pkc-␤ Inhibition In Vivo Prevents Akt S473 Phosphorylation Imentioning
confidence: 64%
“…Diabetic rats had an average plasma glucose level Ͼ25 mmol/L, unaffected by treatment with ruboxistaurin (control 5.78 Ϯ 0.51 mmol/L, STZ 25.7 Ϯ 1.94 mmol/L, STZϩRub 28.5 Ϯ 0.84 mmol/L; P Ͻ 0.01 for STZϩRub versus Con). 28 Figure 9A shows that pAktS473 was increased in the cortex of diabetic rats and that this was inhibited by ruboxistaurin. Data are quantified in Figure 9B.…”
Section: Pkc-␤ Inhibition In Vivo Prevents Akt S473 Phosphorylation Imentioning
confidence: 99%
See 1 more Smart Citation
“…In rats with streptozotocin-induced diabetes, treatment with RAS inhibitor decreased renal VEGF mRNA and simultaneously reduced albuminuria [9,10] . However, in this study, the mechanism of uVEGF decrease was unclear.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, it was reported that VEGF overexpression in diabetic rats [9,10] and in cultured human proximal tubule cells [11] could be attenuated by the administration of renin angiotensin system (RAS) inhibitor. The use of RAS inhibitor led to a decreased incidence of albuminuria in the diabetic rats.…”
Section: Introductionmentioning
confidence: 99%